(3QSGdI cTa GdeVeQ Yf TQM HjJjf dGHf GdYQHis - (3CMeO Hf SdjeGf GdfbTHfOi GdCQhGOis ((3YeQ CfSi Hf GdSjO OjH GdUbYGf s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO ajbhd CMeO GdNGdOi GdfbTHfOi Hf SdjeGf bO SGdfi HYV GdENhGf Yf eYfi HjJjf deYOf GdhdGjI eMji GdOjf GHf GdYQHi aTWQJgeG hTQMJgeG s
(3BNQgG (B:s
(3hNJeJ gPg GdQSGdI HgPg GdCHjGJ abdJ (B: (3MVhQc YfO GdPcQ hbJ hUGdg jJjgc ai CfhGQg hLeGdg hai gPG GdbOQ caGjI dage CQHGH GdOQGjI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs